Physical and functional properties of NSIC Rc160 (Tubigan 14) brown rice flour - Villarica, Kathleen Marie C. (College of Home Economics, University of the Philippines Diliman, 2013)
The physical (color, bulk density, water absorption index, and water solubility index) and functional properties (water absorption capacity, oil absorption capacity, emulsifying capacity, emulsion stability, least gelation concentration, foaming capacity, and pasting properties) of NSIC Rc160 brown rice flour (BRF) were evaluated and compared to that of NSIC Rc160 polished rice flour (PRF). Proximate analysis was first done to assess the chemical composition of the rice flours. The BRF had significantly greater (p < 0.05) amounts of crude fat (2.53%), crude fiber (1.03%), and ash (1.48%) as compared to the PRF. Experimental values for all physical properties tested proved to be significantly different (p < 0.05). The PRF was found to be significantly lighter (p < 0.05) than the BRF. Water solubility index was significantly greater (p < 0.05) for the BRF. Water absorption capacity (1.00 g/g) was significantly lesser (p < 0.05) for the BRF. In terms of pasting properties, the peak viscosity (PV) (2751 cP), trough (1070 cP), breakdown viscosity (1501 cP), and final viscosity (2080 cP) were significantly less (p < 0.05) for the BRF indicating that the PRF is more viscous. The retrogradation (1010 cP) was also significantly less for the BRF which validates the higher PV for PRF and its greater resistance to retrogradation. The acceptability of the BRF in food systems was determined by applying it in cookies. Results of the consumer acceptance test of PRF and BRF cookies showed significant difference (p < 0.05) only in terms of appearance and texture.